Bates' visual guide to physical examination - Bickley, Lynn S.; Lippincott Williams & Wilkins ([Philadelphia] : Lippincott Williams & Wilkins, 2005)
Each of the first twelve modules in the series is devoted to a specific body region or system-letting you focus on specific examination techniques and analytic skills. Six new modules cover assessment strategies for specific patient groups across the life span
vol. 1. Head, eyes, and ears (25:30 min.) vol. 2. Nose, mouth, and neck (18:24 min.) vol. 3. Thorax and lungs (22:40 min.) vol. 4. Cardiovascular : (36:40 min.) vol. 5. Cardiovascular : (17:20 min.) vol. 6. Breasts and axillae (15:20 min.) vol. 7. Abdomen (18:02 min.) vol. 8. Male genitalia, hernias, rectum, and prostate (17:22 min.) vol. 9. Female genitalia, anus, and rectum (21:30 min.) vol. 10. Musculoskeletal system (32:30 min.) vol. 11. The nervous system : (35:54 min.) vol. 12. The nervous system : (21:02 min.) vol. 13. Approach to patient (23:49 min.) vol. 14. Head-to-toe assessment of the adult (38:00 min.) vol. 15. Head-to-toe assessment of the infant (41:30 min.) vol. 16. Head-to-toe assessment of the child (43:18 min.) vol. 17. Head-to-toe assessment of the older adult (37:50 min.) vol. 18. General survey, vital signs, and skin (37:05 min.)
System requirements: Either a consumer-grade DVD player or PC capable of playing NTSC-format DVDs. Coded for all international regions (1-6)
Keywords: Physical Examination -- methods